Effects of Catalytic‐Electrode Thickness on a Hydrogen Sensor Based on Organic Thin‐Film Transistor. Issue 5 (21st December 2017) - Li, Bochang; Lai, Pui To; Tang, Wing Man
Abstract : For a H2 sensor based on pentacene organic thin‐film transistor with palladium (Pd) source/drain (S/D) electrodes as sensing medium, the effects of the electrode thickness on its hydrogen sensing performance are studied. Since the lattice expansion of the S/D electrodes induced by H absorption is restrained by the underlying pentacene layer, the sensitivity of the sensor first increases with the electrode thickness. But then, it decreases with further increase in electrode thickness because larger stress generated at the Pd/pentacene interface by the larger thermal load of thicker electrode during fabrication can degrade the contact between the Pd and pentacene. As a result, experiments show that the sensor with 50‐nm Pd S/D electrodes realizes the highest sensitivity. Moreover, the response and recovery times increase with the electrode thickness because H atoms have to diffuse a longer distance between the electrode surface and the electrode/pentacene interface. Abstract : For a H2 sensor based on pentacene organic thin‐film transistor with palladium (Pd) source/drain (S/D) electrodes as sensing medium, the effects of the electrode thickness on its hydrogen sensing performance are studied.